ANALISA DISTRIBUSI MIKROBA PADA SETIAP KEDALAMAN TANAH LATERIT LAHAN TANAMAN KOPI DENGAN TEKNOLOGI BIOSOILDAM - Widiasmadi, Nugroho (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to test Superbokashi to control soil health and fertility naturally. This research was conducted on land with lateritic soil structures used for coffee plantations by observing the distribution pattern of Electrolyte conductivity levels at each soil depth through microbial activity. Where it spreads through two types of bioholes, namely horizontal and vertical bioholes. This study observed over a period of time through a microcontroller sensor the changes in soil parameters such as: soil acidity level, infiltration rate, electrolyte conductivity level and porosity level which were observed from the soil infiltration rate. Using the simulation method with two (2) types of bioholes, it can be seen the increase in EC at each depth over a certain period of time. This method uses Smart Biosoildam (Biodam) technology which can be simulated to match the actual process (real time). From the observation of the graphs and EC standards, it can be seen that the ability of the soil to provide nutrients in the root growth zone can be used as information to determine the schedule and pattern of planting distribution both during the vegetative growth period and the generative growth period. So that it can be known the effective spacing and biohole spacing in order to be able to provide nutrition during the vegetative and generative periods. The distribution of nutrients can be monitored through sensors that convert analog parameters on the microprocessor into digital information that is sent via wifi in real time. Simulation of sandy beach soil fertility based on microbial population = 108/cfu. Variable 1: The soil fertility value of the electrolyte conductivity/EC value at a depth of 26 cm from 650 uS/cm to 1338 uS/cm on day 35 and from 1338 uS/cm decreased to 1090 uS/cm on day 40. Variable 2: Soil fertility values from electrolyte conductivity / EC values at a depth of 24 cm from 650 uS / cm to 1268 uS / cm on day 35 & from 1368 uS / cm decreased to 1142 uS / cm on day 40.